Mirrored Resiliency: Exploring University Student Narratives of the COVID-19 Pandemic (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2021)
The COVID-19 pandemic has brought increased attention to university student mental health and well-being. In a pandemic research environment, I conducted a narrative inquiry that explored the stories of Canadian undergraduate students who experienced mental distress during the transition from high school to university. In this brief, I aimed to explore an unexpected line of inquiry: the stories of university student resiliency during the COVID-19 pandemic. As I explored the experiences of my student participants, I found a space for narrative learning and mirrored resiliency where I could reflect on my own student experience amidst the pandemic. The circumstances brought about by the pandemic emphasize the need to build capacity for adaptability, resiliency, and well-being.